Religious Improvement Efforts at SMP Muhammadiyah 8 Surakarta - Rizki May Cahyo; Mohammad Zakki Azani (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
Muhammadiyah 8 Junior High School Surakarta is a new school that combines formal and religious schools. In this school, students obtain knowledge or information that has a social and religious nature. The activities include performing Dhuha prayers at the mosque, reading the Koran before the lesson begins, shaking hands with the teacher when entering the school, performing Friday prayers at school, and providing religious counselling so that students do not behave deviantly. in this school, the practice of reading and writing called PAI is carried out every Monday to Thursday, which is before the implementation of learning activities in each class, students will perform Dhuha prayers in the mosque. Then they return to their respective classes to read Al Quran and Iqra. and Learners attend Friday prayers every Friday. At SMP Muhammadiyah 8 aims to develop discipline in students, not only discipline, but also devotion to Allah SWT, moral education and the process of changing religious values in accordance with student morals.